OBTAINING AND ANALYZING CORRELATIONAL MATHEMATICAL MODELS OF THE SIZING PROCESS - Yangiboyev, Ruziboy (Scientific and Technical Journal of Namangan Institute of Engineering and Technology, 2024)
In this article, the influence of incoming and outgoing factors affecting the process of carding yarns in carding machine, as well as the quality of winding on the weaving bobbin, etc., are analyzed. The selected factors in the process of measuring the experiment in accordance with all the requirements of the theory of mathematical planning are the linear density of the yarn, the resistance of the air and the moisture of the raw materials. the possibility of disruption of processes and results is taken into account.